The level of effective organizational climate in Jordanian intermediate university colleges in light of the variables of communication and digital technology - Abdel-Hadi, Laila (Technium Social Sciences Journal, 2025)
This study aimed to identify the level of effective organizational climate in intermediate university colleges in light of the variables of communication and digital technology. The study sample, which was stratified randomly, consisted of (382) faculty members. The descriptive survey method was used in the current study. To achieve the objectives of the study, a questionnaire was developed, and its validity and reliability were verified, the results showed that the degree of availability of an effective organizational climate in intermediate university colleges was average. The study results also showed the presence of statistically significant differences at the significance level (α≤ 0.05) due to the gender variable in favor of the male category, and the absence of statistically significant differences due to the type of college variable, and the absence of statistically significant differences due to the academic rank variable. In light of these results, the study recommended that intermediate university colleges give great importance to the organizational climate by stimulating the conduct of studies and research from time to time to study the conditions of faculty members working in them and their economic, social and psychological problems related to the university work environment